Starting an R&D Project under Uncertainty - Sabien Dobbelaere; Roland Iwan Luttens; Bettina Peters (Tinbergen Institute, 2009)
We study a two-stage R&D project with an abandonment option. Two types of uncertainty influence the decision to start R&D. Demand uncertainty is modelled as a lottery between a proportional increase and decrease in demand. Technical uncertainty is modelled as a lottery between a decrease and increase in the cost to continue R&D. We relate differences in uncertainty to differences in risk premia. We deduct testable hypotheses on the basis of which we empirically analyze the impact of uncertainty on the decision to start an R&D project. Using data for about 4000 German firms in manufacturing and services (CIS IV), our model predictions are strongly confirmed.
Keywords: D21; D81; L12; O31; 330; Investment under uncertainty; R&D; demand uncertainty; technical uncertainty; entry threat; Investitionsentscheidung; Industrieforschung; Entscheidung bei Unsicherheit; Markteintritt; Theorie; Deutschland